2019
DOI: 10.29278/azd.649586
|View full text |Cite
|
Sign up to set email alerts
|

Çakıldak fındık çeşidinde iç meyve iriliğine bağlı olarak biyokimyasal özelliklerin değişimi

Abstract: The study was conducted to determine reletaion in the among biochemical properties with kernel size in Çakıldak cultivar. For this purpose, kernels were divided into three groups as small (9.0-11.0), medium (11.01-13.0) and large (13.01-15.0) according to kernel size. In kernels classified according to kernel size were detected oil ratio, protein ratio, total phenolics content, total flavonoids content and antioxidant capacity (according to FRAP and DPPH assays). While the effect of kernel size on protein rati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 36 publications
1
8
0
Order By: Relevance
“…Unsaturated fatty acids of hazelnuts constitute a valuable source of oil for human nutrition (Garcia et al, 1994). Such differences in protein and oil ratios of hazelnut cultivars were mainly attributed to differences in genetics and ecological conditions (Balık and Beyhan, 2019b;Beyhan et al, 2007), cultural and technical practices (Yılmaz et al, 2019), and harvest times (Farinelli et al, 2001;Seyhan et al, 2007). Pollinator cultivars were also reported to have significant effects on protein ratios of walnuts (Golzari et al, 2016) and chestnuts (Xuhui et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Unsaturated fatty acids of hazelnuts constitute a valuable source of oil for human nutrition (Garcia et al, 1994). Such differences in protein and oil ratios of hazelnut cultivars were mainly attributed to differences in genetics and ecological conditions (Balık and Beyhan, 2019b;Beyhan et al, 2007), cultural and technical practices (Yılmaz et al, 2019), and harvest times (Farinelli et al, 2001;Seyhan et al, 2007). Pollinator cultivars were also reported to have significant effects on protein ratios of walnuts (Golzari et al, 2016) and chestnuts (Xuhui et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…In this study, kernel size was effective in antioxidant activity. Similarly, Yilmaz et al (2019) also reported that the kernel size had an effect on the antioxidant activity. In addition, as observed in the study results, the results differed according to the different antioxidant assays applied in other studies.…”
Section: Resultsmentioning
confidence: 86%
“…Its antioxidants have anticancer and antiatherosclerotic properties, and phytochemicals and phenolic compounds protect against the harmful effects of cancer and oxidative stress (Yılmaz et al, 2019). The nutritional value of hazelnut varies based on cultivar, harvest season, drying method, clonal differences, nutrition, altitude, and habitat (Turan, 2018).…”
Section: Introductionmentioning
confidence: 99%